2019
DOI: 10.22517/25395203.17281
|View full text |Cite
|
Sign up to set email alerts
|

Fisioterapia en la inhibición muscular artrogenica. Revisión de literatura

Abstract: El objetivo de este estudio fue investigar la efectividad de la Fisioterapia en la inhibición muscular artrogénica. Se realizaron búsquedas en las bases PEDro, Embase, Scielo y PubMed para identificar ensayos controlados aleatorios (ECA) de intervenciones de Fisioterapia en la inhibición muscular artrogénica. La literatura incluyo referencias en inglés, español y portugués, publicados entre Enero de 2000 y Junio de 2017. Se identificaron 7 ensayos clínicos que se incluyeron en esta revisión y 4 Revisión Sistem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…Regarding the normalized force in knee flexion and extension with both legs MVIC in the CG, there was a statistically significant difference since the p value is 0.013, an initial median of 8.26, intermediate of 9.41, and final of 10.7 for a delta of 1.22 between the final and initial assessment; while for the IG the delta between the final assessment, with a median of 9.40, and the initial one with a median of 7.83, was 1.25, being slightly higher for the IG. This is in line with the study by Bartholdy in [1], in which he found a statistically significant difference in favor of American College of Sport Medicine interventions with respect to knee extensor strength (SMD difference: 0.448 (CI 95%: 0.091-0.805)). In the Bartholdy study [1], no non-American College of Sport Medicine interventions were observed and associations between increased knee extensor strength and changes in pain and/or disability were assessed using meta-regressions that indicated that increases in knee extensor strength of 30-40% would be necessary for a likely concomitant beneficial effect on pain and disability, respectively.…”
Section: Increased Strength With Both Legs and Symmetry Between Themsupporting
confidence: 90%
See 4 more Smart Citations
“…Regarding the normalized force in knee flexion and extension with both legs MVIC in the CG, there was a statistically significant difference since the p value is 0.013, an initial median of 8.26, intermediate of 9.41, and final of 10.7 for a delta of 1.22 between the final and initial assessment; while for the IG the delta between the final assessment, with a median of 9.40, and the initial one with a median of 7.83, was 1.25, being slightly higher for the IG. This is in line with the study by Bartholdy in [1], in which he found a statistically significant difference in favor of American College of Sport Medicine interventions with respect to knee extensor strength (SMD difference: 0.448 (CI 95%: 0.091-0.805)). In the Bartholdy study [1], no non-American College of Sport Medicine interventions were observed and associations between increased knee extensor strength and changes in pain and/or disability were assessed using meta-regressions that indicated that increases in knee extensor strength of 30-40% would be necessary for a likely concomitant beneficial effect on pain and disability, respectively.…”
Section: Increased Strength With Both Legs and Symmetry Between Themsupporting
confidence: 90%
“…This is in line with the study by Bartholdy in [1], in which he found a statistically significant difference in favor of American College of Sport Medicine interventions with respect to knee extensor strength (SMD difference: 0.448 (CI 95%: 0.091-0.805)). In the Bartholdy study [1], no non-American College of Sport Medicine interventions were observed and associations between increased knee extensor strength and changes in pain and/or disability were assessed using meta-regressions that indicated that increases in knee extensor strength of 30-40% would be necessary for a likely concomitant beneficial effect on pain and disability, respectively.…”
Section: Increased Strength With Both Legs and Symmetry Between Themsupporting
confidence: 90%
See 3 more Smart Citations